Thibault and Science I. Measure, Distances and Proportions in the Circle - János Majár; Zoltán Várhelyi (Bern Open Publishing, 2015)
In this paper we investigate the basic mathematical and philosophical tool of Gérard Thibault d'Anvers, the Circle. One of our main goals was to describe the Circle with coordinate geometry, and to estimate the rate of accuracy of his work. Furthermore, we also wanted to test the statements made by Thibault in his fencing manual, Academy of the Sword [Thibault, 1630; Greer, 2005]. To do this, we compared his observations and calculations with the results of available modern day and historical anthropometrical data sets. Based on our results, we also want to give some practical information about Thibault system for the fencers who study his art in our time.